Study of mutual fund styles, classification and performance. - Kwan, Kah Kit. (2008)
This Applied Research Project involves using Sharpe’s methodology to estimate the asset allocation values of a sample of twenty-two Australian Balanced Funds by regressing the monthly returns of these funds with five selected asset classes.